HAK DAN PERLINDUNGAN ANAK MENURUT HUKUM HINDU - Ariani, Nyoman Wiraadi Tria; Sari, Ni Putu Yunita (Institut Agama Hindu Negeri Gde Pudja Mataram, 2022)
Children according to Hindu law have rights and obligations as children. These rights are generally obtained from the time the child is still in the womb until the time the child dies. Child protection is actions to guarantee, protect children and children's rights so that they can grow and develop. This study uses a literature research method or literature study that examines the Hindu legal order in understanding the rights and protection of children. Hindu law emphasizes that parents are obligated to provide protection for children in all matters including the fields of education, health and social welfare of children. The study of Hindu law is in accordance with applicable law in Indonesia, namely the implementation of child protection that is considered in making decisions relating to the future of the child. continuously regardless of ethnicity, religion, race, or class.